Idiopathic Sudden Sensorineural Hearing Loss: Predictive Factors for Hearing Recovery - Salvador, Pedro (2020)
Aims: This study aimed to evaluate treatment outcome of idiopathic sudden sensorineural hearing loss (ISSHL) and to investigate predictive factors of hearing recovery. Study Design: Retrospective study. Material and Methods: This study included 77 patients diagnosed with ISSHL, from January 2009 to December 2018. All patients were treated initially with systemic steroids (SS) and intratympanic steroids (ITS) were offered as salvage treatment to patients with incomplete recovery. Study population was divided into two groups according to achievement of hearing recovery, defined by an improvement in pure tone average (PTA) > 15 dB and a final PTA < 45 dB. Multivariate logistic regression analysis was performed to identify clinical predictors of recovery.  Results: Overall, there was a mean PTA improvement of 22.1±16.3 dB and a recovery rate of 55.8%. We found poorer recovery rate in patients with profound hearing loss (p<0.01), later treatment (p<0.01), hyperlipidemia (p=0.02) and venous insufficiency (p=0.03).However, multivariate analysis identified degree of hearing loss (profound, OR 16.9, p=0.001) and duration from onset of symptoms until treatment (≥ 7 days, OR 12.5, p=0.002) as the only independent predictive factors of poor hearing outcome. Conclusion:Our results support the importance of early initiation of treatment. A profound hearing loss at admission was as a poor prognostic factor.